Leadership in Action : Developing Anticipation - A Reply - Smith, Cheryl B. (Center for Creative Leadership, 1999)
Learning from experience involves, among other things, the ability to anticipate and to recognize when new behaviors, skills, and attitudes are required and to see when current approaches are not working (Van Velsor and Guthrie, 1998).